Diseño e implementación de un banco de pruebas para instrumentos de medición de nivel y flujo para el laboratorio de investigación de automatización y control de la carrera de ingeniería electromecánica de la universidad técnica de Cotopaxi. - Cuenca Satan, Danny Javier (2020)
This project describes the development of technology for an optimal production process with the use of sensors, transmitters, signals, and interfaces with process monitoring options. Fundamentally, it involves the development of an industrial level and flow measuring instrument testbed which performs a water pumping process between two vessels (main and reserve) that are interconnected with pipes and valve; in this process, measurements of physical level and flow variables are made, which allows the user, with the data obtained to produce an analysis of precision using some arguments established in the theory of errors. The project is divided into three stages. In the first stage, the bibliographic concepts used in the instrumentation and control area are described in a general way, which are based on a description, characteristics and appropriate use of the equipment, components, and accessories of which the test bench of measuring instruments is composed, additionally to the design of the model. The second stage details the characteristics and operating parameters of each level and flow sensor, plus the elements to be used; calculation procedures describe it as different parameters of some elements and equipment were dimensioned; a structural analysis simulation is also performed to verify the mechanical strength of the composition and designs of the measuring instrument test bench. In the last stage, the configuration of each sensor (ultrasonic level and turbine flow) is carried out, as well as the acquisition of the measured values through the use of a microcontroller (Arduino) as an acquisition card (DAQ) to carry out with the data obtained a precision analysis applying the theory of measurement errors; through graphs generated in Excel, researchers observe the behavior of each sensor in different parameters; according to the results obtained, laboratory practice guides were created for students to carry out the connections and check each measuring instrument as specified in the this project.